2013
DOI: 10.1038/ijo.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

Obesity development in caspase-1-deficient mice

Abstract: Caspase-1 is a member of the intracellular cysteine protease family that mediates inflammation through the activation of the cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18). As mice lacking IL-18 become obese and insulin resistant, and both IL-18 and IL-1β have a role in overall energy balance, we sought to determine whether caspase-1 deficiency also causes obesity. Male and female caspase-1-deficient (caspase-1-/-) and control (wild-type (WT)) mice were fed either a high-fat (HF, 45% of kcal) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…Also, pancreatic β-cell death and insulin resistance in T2DM have been associated with IL-1β secretion mediated by the ROS-TXNIP axis, thereby enhancing NLRP3 activation (Zhou et al, 2010). This involvement of ROSTXNIP in T2DM is consistent with the requirement for ROS in the NLRP3 inflammasome pathway (Wang et al, 2014a). Therefore, the NLRP3 inflammasome may contribute to the pathogenesis of T2DM via the TXNIP protein (Wang et al, 2014a).…”
Section: Nlrp3 Inflammasome Activation and Regulationsupporting
confidence: 84%
See 2 more Smart Citations
“…Also, pancreatic β-cell death and insulin resistance in T2DM have been associated with IL-1β secretion mediated by the ROS-TXNIP axis, thereby enhancing NLRP3 activation (Zhou et al, 2010). This involvement of ROSTXNIP in T2DM is consistent with the requirement for ROS in the NLRP3 inflammasome pathway (Wang et al, 2014a). Therefore, the NLRP3 inflammasome may contribute to the pathogenesis of T2DM via the TXNIP protein (Wang et al, 2014a).…”
Section: Nlrp3 Inflammasome Activation and Regulationsupporting
confidence: 84%
“…This involvement of ROSTXNIP in T2DM is consistent with the requirement for ROS in the NLRP3 inflammasome pathway (Wang et al, 2014a). Therefore, the NLRP3 inflammasome may contribute to the pathogenesis of T2DM via the TXNIP protein (Wang et al, 2014a). However, the mechanisms that induce ROS generation in response to metabolic stress, such as chronic hyperglycemia, remain incompletely understood.…”
Section: Nlrp3 Inflammasome Activation and Regulationsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, it was also observed that NLRP3, ASC, and caspase-1 deficiency protected from HFD-induced obesity 106 . However, a recent study reported contradictory results that mice lacking Casp1 were more obese than control mice including having increased fat mass compared with controls 121 . The difference may be due to the variation in intestinal microbiota in mice raised in different animal facilities, as intestinal microbiota has been demonstrated to play a significant role in metabolic diseases 122 .…”
Section: Inflammasomes In Diseasementioning
confidence: 97%
“…It is characterized by a reduction in the ability of insulin to stimulate glucose utilization, insulin resistance and inadequate pancreatic β-cell insulin secretion in response to hyperglycemia [7,10]. Elevated level of IL-1β and limited beta-cell function are two primary predictors for the development of T2DM [75]. Pioneering studies have demonstrated the contribution of NALP3 inflammasome in the pathogenesis of T2DM.…”
Section: The Inflammasome In Type 2 Diabetesmentioning
confidence: 99%